2003
DOI: 10.1093/jn/133.11.3546
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Elemental Iron Powders to Rats Is Less than Bakery-Grade Ferrous Sulfate and Predicted by Iron Solubility and Particle Surface Area

Abstract: Foods are fortified with elemental forms of iron to reduce iron deficiency. However, the nutritional efficacy of current, commercially produced elemental iron powders has not been verified. We determined the bioavailability of six commercial elemental iron powders and examined how physicochemistry influences bioavailability. Relative biological value (RBV) of the iron powders was determined using a hemoglobin repletion/slope ratio method, treating iron-deficient rats with repletion diets fortified with graded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
90
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 25 publications
1
90
5
Order By: Relevance
“…Since iron solubility, iron retention, transport efficiency, and uptake efficiency percentages can be used as bioavailability predictors [8,26,27] , our results showed that three of the four infant cereals analyzed after phytase treatment increased iron bioavailability. The source of iron used for the enrichment of infant cereals (elemental iron) plays an important role in iron solubility [28] ; in this regard, values found in our study were lower than those reported by other authors [29,30] for the same element, probably due to the phytate content or fiber components from cereals, the different pH conditions applied for the assays [29] , or the previously reported the inhibitory effect of calcium on iron availability [10] since infant cereals used in this study were calcium-enriched. Differences in iron bioavailability parameters between dephytinized infant cereals could indicate that other components of infant cereals can also decrease iron bioavailability; in this regard, it has been reported that some dietary fiber components can bind mineral ions decreasing their bioavailability [30,31] .…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Since iron solubility, iron retention, transport efficiency, and uptake efficiency percentages can be used as bioavailability predictors [8,26,27] , our results showed that three of the four infant cereals analyzed after phytase treatment increased iron bioavailability. The source of iron used for the enrichment of infant cereals (elemental iron) plays an important role in iron solubility [28] ; in this regard, values found in our study were lower than those reported by other authors [29,30] for the same element, probably due to the phytate content or fiber components from cereals, the different pH conditions applied for the assays [29] , or the previously reported the inhibitory effect of calcium on iron availability [10] since infant cereals used in this study were calcium-enriched. Differences in iron bioavailability parameters between dephytinized infant cereals could indicate that other components of infant cereals can also decrease iron bioavailability; in this regard, it has been reported that some dietary fiber components can bind mineral ions decreasing their bioavailability [30,31] .…”
Section: Discussioncontrasting
confidence: 87%
“…The source of iron used for the enrichment of infant cereals (elemental iron) plays an important role in iron solubility [28] ; in this regard, values found in our study were lower than those reported by other authors [29,30] for the same element, probably due to the phytate content or fiber components from cereals, the different pH conditions applied for the assays [29] , or the previously reported the inhibitory effect of calcium on iron availability [10] since infant cereals used in this study were calcium-enriched. Differences in iron bioavailability parameters between dephytinized infant cereals could indicate that other components of infant cereals can also decrease iron bioavailability; in this regard, it has been reported that some dietary fiber components can bind mineral ions decreasing their bioavailability [30,31] . Commercial infant cereal (Multicereals) showed the highest values of iron bioavailability parameter measures which can be justified because of its lower molar ratio of phytate to iron, compared to eight cereals-honey, rice cream and Glutenfree cereals.…”
Section: Discussioncontrasting
confidence: 87%
“…it is less soluble at higher pH. It should be taken into account that the previously cited bioavailabilities of carbonyl iron (Devasthali et al 1991;Swain et al 2003) were obtained at gastric pH below 2. Because of relatively high pH of gastric content in suckling piglets, the negative effect of gastric pH on carbonyl iron utilization could be expected.…”
Section: Discussionmentioning
confidence: 88%
“…With carbonyl iron, however, only that fraction solubilized by gastric acid is available for absorption. According to Swain et al (2003) the bioavailability of carbonyl iron in rats is 64% of that of ferrous sulphate. Devasthali et al (1991) found in humans that the bioavailability of carbonyl iron was about 70% of that of ferrous sulphate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation